Influence of thermal and gravity driven flows on an arctic fjord wind regime : a case study with numerical simulations - Dusch, Matthias (2018)
Although the Ny-Ålesund, Svalbard, wind field is of great interest to various ongoing arctic research topics the governing processes are not systematically studied in-depth so far. This thesis tries to increase the knowledge on the interaction between two relevant processes: The thermally driven land-sea-breeze system and gravity driven katabatic flow. A related case study for the period April 14th 12 UTC till April 16th 12 UTC based on numerical simulations using the Weather Research and Forecasting Model is presented. Extended sensitivity runs with increased sea surface temperature and additional sea ice were made to separate the different processes. Main focus within this thesis is the northwest to southeast transect Kongsfjorden, Kongsvegen, Sveabreen and Isfjorden. This transect is of interest as it connects two fjord-glacier systems with different slope aspects at the joint Kongsvegpasset. Katabatic forcing was present with comparable strength throughout all simulation runs at both glaciers. Thermal wind forcing shows a sea surface temperature dependant behaviour and vanishes if sea ice is added around Svalbard. A partial momentum budget is calculated to estimate the structure and magnitude of thermal wind and katabatic forcings. Key parameters within the partial momentum budget were calculated in various forms to establish a robustness of the individual terms. The katabatic term was shown to be quite robust. The thermal wind term is more sensitive to the definition of the governing parameters. It is particularly sensitive to the horizontal gradient dtheta/dx. by Matthias Dusch Masterarbeit University of Innsbruck 2018